EFFECT OF CRUDE EXTRACTS AND ESSENTIAL OILS OF MEDICINAL PLANTS AGAINST SCLEROTINIA SCLEROTIORUM IN POTATO FIELDS - Ojaghian, Seyedmohammadreza (Potato Journal, 2019)
This study was carried out to determine inhibitory effect of crude extracts and essential oils of aromatic plants against Sclerotinia sclerotiorum in potato fields in Bahar and Lalehjin, Iran during cropping seasons of 2015 and 2016. The results showed that crude extracts of cinnamon and ginger at concentrations 5 g/l as well as essential oils of coriander,lavender thyme, savory and eucalyptus at concentration 50 Î¼l EO/ml had potential to significantly reduce incidence of potato white mold. This is the first study about inhibitory effect of crude extracts and essential oils of aromatic plants against potato white mold under field condition.